Experiencing Stress during a Coronavirus COVID-19 Pandemic: the Perspective of an Ambulance Worker - Globuytė, Monika; Gutienė, Virginija; Freimanienė, Aušra (Slauga. Mokslas ir praktika, 2021)
Ambulances are currently working in particularly difficult conditions, facing non-standard situations on a daily basis, receiving a wide range of new information, changing working conditions and increased workloads. Therefore, the aim of this work is to assess the stress experienced during a coronavirus COVID-19 pandemic from the perspective of ambulance personnel. The aim of the study - to evaluate the stress experienced during a pandemic from the point of view of ambulance staff. Research methods. Analysis of scientific literature; questionnaire survey; descriptive statistical analysis. Results. Assessing the stress experienced during the coronavirus COVID-19 pandemic, it was found that the increase in stress at work was usually caused by the unsafe work environment at calls, long-term presence with personal protective equipment, changed work specifics, work organizational aspects. The level of stress was increased by fear of infecting the family, friends and oneself with the virus, an increase in the number of patients and future physical isolation after contact with a (potentially infected) patient with coronavirus Coclusions. After reviewing the scientific literature and analyzing the definitions of stress provided by different authors, we could describe stress as follows: stress is the body’s response to various unpleasant emotional experiences - the body’s response to changes that require response, regulation of physical, psychological and emotional adjustment. According to the study, the longer the work experience of employees, the more they are afraid of being infected with coronavirus. There was increased emotional tension, mood swings, and impaired concentration. The stress experi-enced at work affected the physical and mental health of employees, decreased motivation to work, and reduced the quality of work.